A Balanced Dual-Intracavity Dual-Mode Interlocking Method for Fiber Laser Self-Reference Wavelength Stabilization - Liuxin Zhang; Kang Ying; Guochao Wang; Haoyang Pi; Zhaoyong Wang; Yanguang Sun; Fang Wei; Youzhen Gui; Qing Ye; Haiwen Cai (IEEE Photonics Journal)
The laser frequency stabilization technology is very important in the development of laser applications, and the improvement of this technology has tend to further expectations for portability and low cost, in addition to the realization of strict frequency control. In this context, we construct a dual-cavity laser frequency stabilization system based on an intracavity dual-mode self-reference mechanism. With this approach, we achieve remarkable results with a laser frequency drift of about 6.6 kHz and an Allen deviation (ADEV) of 10−13 levels over an integration time scale from 0.01 s to 1000 s. Notably, the solution achieves one of the best results without the need for an external reference structure. This work provides a way to realize wavelength-stabilized laser sources by interlocking two DFB lasers. This approach is distinguished by its simplicity and cost-effectiveness, making it a promising option for a variety of applications outside of the laboratory environment.